Pedagogical perspective on ChatGPT’s effectiveness as a learning tool for ESL writing - Goh, Poh Shen (2024)
The arrival of ChatGPT in the education scene has garnered many different perspectives various stakeholders. In particular, there were many concerns regarding the ethical use of ChatGPT along with the divide in the view on ChatGPT’s pedagogical value to English second language (ESL) students in terms of their writing. Thus, due to an additional lack of studies done on exploring the various pedagogical value of ChatGPT, this exploratory study was conducted with these two research objectives in mind: “a) To inquire the perspectives of UTAR lecturers on the benefits and drawbacks of using ChatGPT as a learning tool in ESL writing.”, and “b) To critically analyse the perspectives of UTAR lecturers’ perspectives on the application of ChatGPT in ESL writing classrooms along with its potential challenges and recommendations.”. A semi-structured interview was conducted with five UTAR lecturers whose expertise were in the field of writing pedagogy to inquire their views on ChatGPT with regards to the research objectives. The results of the interviews reveal that lecturers as a whole had mixed perspectives regarding the A.I. chatbot. Most agree that while ChatGPT can present various benefits to ESL students in improving their writing, the overreliance can cause students’ intellectual abilities to be stunted and risking the practice of plagiarism. The lecturers were also receptive towards the application of ChatGPT in ESL writing classrooms but raised concerns on the challenges of students misusing ChatGPT and the threat to student and teacher relationships. Lastly, lecturers also suggested various recommendations emphasising proper guidelines and ethics to be instilled, redefining the role of teachers, and modifying assessments. Recommendations were also given to further research the various areas addressed in this study.